High-Input-Impedance Four-Input Single-Output Voltage-Mode Biquadratic Filter with Only VDTAs and Grounded Capacitors - Satansup, Jetsdaporn; Pukkalanun, Tattaya; Tangsrirat, Worapong (My University, 2022)
This paper presents a voltage-mode universal biquadratic filter with voltage differencing transconductance amplifiers (VDTAs) as active components. The proposed filter comprises four inputs and a single output and can perform all five general biquadratic filter functions, namely lowpass, bandpass, highpass, bandstop, and allpass responses, without modifying the circuit architecture. It also offers the advantages of resistorless implementation with only two grounded capacitors, orthogonal adjustment of the natural angular frequency and the quality factor, as well as the absence of any constraint related to the values of input signals. Moreover, because the circuit contains all of the high input impedance levels, it may be cascaded without the requirement of additional buffers. The suggested filter's functioning has been validated by simulations using the PSPICE application.
Keywords: biquadratic filter; electronically tunable; universal filter; Voltage Differencing Transconductance Amplifier (VDTA); voltage-mode circuit